Russell's world : a story for kids about autism - Amenta, Charles A. (Charles Anthony); Amenta, Charles A. (Charles Anthony) (Washington, DC : Magination Press, 2011)
Describes the daily life, likes and dislikes, and habits of Russell Amenta, who is a happy boy despite being severely autistic.
Originally published as: Russell is extra special. New York : Magination Press, c1992.
Kirkus Review
Publisher's Weekly
Kirkus Review, April 2011
Publisher's Weekly, March 2011
4.1
Keywords: Amenta, Russell -- Mental health -- Juvenile literature; Amenta, Russell; Amenta, Russell -- Mental health; Autism -- Juvenile literature; Autistic children -- Juvenile literature; Autism; Autistic children; Autism; Autistic children; Picture books for children